A body-force model for waterjet pump simulation. (September 2019) - Eslamdoost, Arash; Vikström, Marko
Abstract: The role of waterjet pump is to generate thrust by increasing the flow head. Details of the flow inside waterjet pump are important when pump performance is of the main interest. However, in waterjet self-propulsion, pump induced effects are of the main interest rather than the details of the flow inside the pump. This permits simplification of pump models when using numerical methods for simulating the flow. In order to find a robust and yet accurate pump model suitable for Computational Fluid Dynamics based methods, models of different sophistication level are studied in this paper. First, a Sliding Mesh approach, which is capable of capturing the flow details, is validated against a set of cavitation tunnel measurements. Then a series of simpler models, i.e. Moving Reference Frame technique and three different body-force models, are studied and their results are compared to the ones obtained from the Sliding Mesh approach. The results indicate that one of the body-force models which takes the guide vanes as well as the impeller induced flow swirl into account has the best compromise between the robustness and accuracy among the investigated pump models.